Histone variants: key regulators of inflammation in cell dedifferentiation and transdifferentiation - Vinciguerra, Manlio; Tsoneva, Desislava K. (Frontiers in Immunology, 2025)
Histone variants are specialized isoforms of histone proteins that play crucial roles in regulating chromatin structure and function, influencing transcription, DNA repair, and cell cycle progression. Their dynamic incorporation into nucleosomes impacts gene expression and cellular identity, particularly in the context of inflammation during cell dedifferentiation and transdifferentiation. This mini-review provides a comprehensive overview of the role of histone variants in these processes, highlighting their significance in modulating inflammatory responses and cellular plasticity. We discuss mechanisms by which histone variants influence chromatin architecture and gene regulation, the interplay between histone variants and inflammatory pathways, and the specific roles of key histone variants such as H3.3, H2A.Z, and MacroH2A in dedifferentiation and transdifferentiation. Additionally, we explore the potential therapeutic implications of targeting histone variants to modulate inflammation and cellular plasticity in diseases like cancer and chronic inflammatory conditions. By summarizing existing knowledge and identifying gaps in understanding, this review underscores the importance of histone variants in inflammation-related cell plasticity and suggests future research directions further elucidating their roles and therapeutic potential.